AKIBAT HUKUM WANPRESTASI PADA KASUS PEMBATALAN KONSER MUSIK - Hardian Iskandar (Jurnal Justiciabelen, 2019)
Due to legal defaults at music concerts result in: First paying for losses that have been experienced by one of the parties. Second, it can result in the cancellation of the agreed agreement. Third, there is a risk transfer and Fourth, paying the case for the case filed before the judge (court). The form of payment intended in this case is the return of tickets by the parties / organizers of music concerts.Costs are any money (including costs) that must be incurred in real terms by the injured party, in this case as a result of default. Whereas the term "loss" is a declining condition (decrease) in the value of the creditor's wealth as a result of a default from the debtor. While what is meant by "interest" is a profit that should be obtained but not obtained by the creditor because of defaults from the debtor.